Gender, job position and sex ratio of police officers as predictors of perception to sexual harassment. - Torre, Ernie L.; Postolero, Jenny Mae M. (2012.)
The study was conducted to find out the perception of police officers to sexual harassment with respect to their gender, job position and sex ratio. The respondents were composed of 12 female police officers and 64 male police from San Joaquin, Guimbal, Igbaras, Tubungan, Tigbauan and Oton. A five-point likert scale questionnaire with 1 as 'definitely not a problem' and 5 as 'definitely a problem' including situational items related to sexual harassment was used. Results showed that male and female officers regardless of their job position and sex ratio perceived sexual harassment as a problem when it is perpetrated by male and by persons of high social ranking. But they tend to consider sexual harassment as not a problem when it involves female as sexual agressors.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Police Officers; Sexual Harassment